The Effect Of Work-Life Balance On Well Being With Supervisor Support As A Moderating Factor - Rahmadhani, Romi; Syahrizal (Universitas Negeri Padang, 2024)
The aim of this research is to about. (1)the influence of work Umrah travel employess in Bukittinggi City (2) Influence supervisor support for the well being of umrah in the Bukittinggi City (2) The influence of Work Life Balance on the Well Being of Umrah Bukittinggi City with Supervisor Support a mmoderating variable The type of research quantitative descriptive research ,the data collection technique is trough distributing questionnaires distribute via google form to Umrah travel employee in Bukitinggi City. Result the research is (1) there is a significant influence between Work Life Balance towards the Well Being of Umrah Travel emplpoyees in Bukittinggi City (2) There are significant influence of Supervisor Support on the Well Being of Travel employees Umrah in Bukittinggi City (3) Has a significant influence on Work Life Balance toward the Well Being of Umrah Travel employees in Bukittinggi City with Support Supervisor as a moderating variable